Mechanics Hall at 111 Huntington Avenue, ca. 1955 - Unknown (Tufts Archival Research Center, 2005)
Street-level view west-southwest of Mechanics Hall, located at 111 Huntington Avenue. The facade of the building faces east-southeast. Street lights and parking meters line Huntington Avenue. A truck is parked in front of Mechanics Hall. Designed by William Gibbons Preston, 1881; demolished, 1959 7 3/4 x 7 1/2, 9 7/8 x 8 overall Photographs